Audit Quality and Earnings Management: Evidence from Sri Lanka: Food & Beverage and Hotel Sectors - C. J. Randenigala; M. R. P. Wijesinghe (Kelaniya Journal of Management)
The company's earnings are crucial for investors' decision-making since they provide emblems about value-creating ability. However, with the possibility of manipulating earnings, the whole purpose of financial reporting becomes valueless. External independent auditing can be identified as a control mechanism that minimises earnings management. This study examines the impact of audit quality on earnings management in the food and beverage sector and hotel companies in the Colombo Stock Exchange from 2013 to 2019. The real earnings management approach and total accruals are used to measure the earnings quality, while audit firm size, presence of the audit committee, frequency of the audit committee meetings and audit timeliness are the audit quality proxies. The study used regression analysis as the main analysis tool, and the findings reveal the existence of earnings management in the food and beverage and hotel sectors. Fascinatingly, audit quality does not significantly impact earnings management in the food and beverage sector, while it exists in the hotel sector. Moreover, companies' size and leverage significantly impact earnings management in both sectors. These findings suggest that effective regulation and monitoring are necessary to improve audit quality for both sectors, especially in the hotel sector companies in Sri Lanka. Hence, enhancing audit quality would minimise earnings management and improve earnings quality, which is instrumental to the decision-makers, especially investors and creditors. Henceforth, we suggest improving the audit quality in the food and beverage and hotel sectors and enhancing disclosure requirements such as research and development expenses, audit time, and non-audit services.